Boom-Bust Cycles in Housing : The Changing Role of Financial Structure - Schnure, Calvin (Washington, D.C. : International Monetary Fund, 2005)
Why are housing markets so prone to boom-bust cycles? The mortgage market structure prior to the Savings and Loan crisis contributed to the volatility in real housing activity which, in turn, amplified the volatility in housing prices. The subsequent development of a national, market-based system of securitized mortgage finance has damped this boom-bust cycle. We test whether deviations of actual housing prices from values forecast by a model based on economic fundamentals have responded to the change in financial structure, and find that pricing errors have fallen significantly since the mid-1980s. Tests of the relative importance of the change in financial market structure versus the reduction of inflation over this period indicate a primary role for market structure in improving pricing efficiency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet